ACTIVITIES OF THE HARWARD INSTITUTE OF UKRAINIAN STUDIES AFTER 1991 AIMED AT NATIONAL IDENTITYPRESERVATION (BASED ON THE UKRAINIAN LANGUAGE PERIODICS ASSESSMENT) - BILOVUS, Lesia; HOMOTIYK, Oksana (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The article is devoted to the issue of «Ukrainian Harvard» functioning after 1991 as the integrated center of Ukrainian studies with a broad, permanent, research, pedagogical and publishing activities. Due to this, Ukrainian community gained the opportunity to access all world libraries, the right to vote in science, the legalization of our position (as an independent party) in controversial issues of a scientific nature, important cultural legitimacy. It also gained the authoritative basis for the further expansion of Ukrainian studies in North America, and thus, createdthe academic platform from which we are able to speak to the intellectual world, including the United States – the world that develops the political outlook and influences the real political activity of any state. Thus, the Ukrainian Research Institute of Harvard University (UNIGU) was meant to become the scientific educational center for Ukrainians aimed at preservingtheir national identity. However, there is no research of UNIGU’s activities through the prism of Ukrainian-language periodicals, which determines the need to study this scientific problem as one of the important aspects of the national identity preservationin the diaspora and defines the relevance of our study. The article is based on the publications of the following newspapers «Svoboda», «Mist» and «Chas i Podii» that were used as a primary source for our research. Before the Ukraine's restoration of independence, UNIGU's efforts were focused on supporting of state-building processes in Ukraine. Today, based on the materials from Ukrainian-language periodicals of the US diaspora, the institution's work, aimed at the national identity preservation, constitutes in spreading previously started programs: increasing of the financial base for the popular Summer School of Ukrainian Studies, replenishment of the library collection of Ukrainian books, funds assignment for important research projects, such as, for example, as the Holodomor of 1932-33, the Ukraine of the 20th century, the millennial Christian heritage of Ukraine, and others. In recent years, the Institute has been trying to respond to modern needs: to collect and analyse the new information about Ukraine, establish contacts, organize conferences, carry out joint publishing projects with other research centers, train new staff, who are gradually taking up the baton of Ukrainian science from the older generation.